Pengaruh Edukasi terhadap Tingkat Pengetahuan Remaja Putri tentang Anemia di Dusun III Kakabai, Desa Nunkurus - Avelina Paskalia Gusman; Maria Magdalena Theofila Duka (CV. ALIM'SPUBLISHING, 2026)
Anemia is a condition with hemoglobin and erythrocyte levels lower than normal, which is 12 grams/dl for adolescents. Iron deficiency anemia in adolescent girls is at higher risk because it causes a decrease in immunity, making them susceptible to health problems. One of the causes is the lack of knowledge of adolescent girls about healthy lifestyles and self-motivation regarding the importance of balanced nutrition in preventing anemia. The purpose of this study was to determine the effect of education on the level of knowledge of adolescent girls about anemia. The type of research used was quantitative research with a quasi-experimental research design with a pre-test-post-test research design. The sample consisted of 90 adolescent girls. The results showed that before being given education, the majority of respondents were in the sufficient category (45.6%), while after being given education, the majority were in the good category (84.4%). The results of this study showed that there was a significant difference in the level of knowledge of adolescent girls about anemia before and after being given education with a significance value of 0.000, which means there was a significant effect of education on the level of knowledge of adolescent girls about anemia.